Sejarah Perkembangan Akuntansi Syariah; Tinjauan Literatur Islam - Zuwardi MA; Hardiansyah Padli (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2020)
This study aims to examine the development of Islamic accounting since the issuance of the letter al baqoroh 282 to the present practice of Islamic financial institutions. A qualitative approach with content analysis in Islamic literature is carried out to describe the historical portrait of Islamic accounting. the result is the development of accounting in the Islamic era along with the trade culture of the Arab nation, which is increasingly developing with the concept of accountability in Islam and increasingly has many variants according to the times. This research also proves that the current sharia accounting practices do not copy western accounting but have a scientific historical basis in practice in the golden age of Islam.